The New Music Industries - Hughes, Diane. author. aut Link
XIX, 137 p. 11 illus.
Keywords: This research-based book outlines career models for artists, methods of creative engagement, artistic options including individuality and branding, production practices, the realities of being a musician in the new industries, and implications for popular music education. Due to the profound effects of the digitisation of music, the music industries have undergone rapid transformation. The former record label dominated industry has been supplanted by new industries, including digital aggregators, strategists and online platforms. These new music industries now facilitate ‘direct’ access to both artists and their music. While such accessibility and the potential for artist exposure have never been greater, the challenge to stand out or to even navigate a musical career pathway is formidable. A useful resource for musicians and educators, this text highlights the ways in which the new music industries facilitate increased opportunities for 21st Century popular musicians to collaborate, communicate and interact with others interested in their music. Associate Professor Diane Hughes is a lecturer in Vocal Studies and Music at Macquarie University, Australia. Her research areas include the singing voice, pedagogy, film and sound, recording practices, the music industries, and popular music and song. She is currently the National President of the Australian National Association of Teachers of Singing Ltd. Professor Mark Evans is the Head of the School of Communication at the University of Technology, Sydney, Australia. He is Series Editor for Genre, Music and Sound and is currently Editor for The International Encyclopedia of Film Music and Sound. He holds an Australian Research Council (ARC) grant to design an artistic and environmental map of the Shoalhaven basin in New South Wales, Australia. Dr Guy Morrow is a lecturer in Arts Industries and Management at Macquarie University, Australia. He focuses on understanding how artists are managed, both in terms of direct artist management and also through cultural policies. By examining the relationship between artists and managers, Guy generates core-related insights in the creative industries. He is currently the Secretary of the International Music Business Research Association. Dr Sarah Keith is a lecturer in Music and Media at Macquarie University, Australia. Her research areas includes popular music studies, Korean and Japanese popular music, other East Asian popular musics, the music industries, music and cultural policy, music and screen media, music and performance technologies and computer-mediated composition. .